2021
DOI: 10.3390/biom11060821
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Proteomic and Metabolomic Analysis of the Testes Characterizes BDE-47-Induced Reproductive Toxicity in Mice

Abstract: A representative congener of polybrominated diphenyl ethers in the environment, 2,2′,4,4′-tetrabromodiphenyl ether (BDE-47), is associated with male reproductive toxicity, yet the underlying mechanisms remain largely unclear. In this study, mice were administered environmentally relevant concentrations of BDE-47 for six weeks. Histopathological observations showed that BDE-47 induced inflammatory reactions and damaged the testes. By conducting an integrated proteomic and metabolomic analysis coupled with a bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…No significant difference between sperm morphology of exposed and control groups was observed in this study; however, some sperm motility parameters were impaired in some exposed groups. In another BDE-47 study, histopathological examination of mice exposed to 1.5, 10, and 30 mg/kg of BDE-47 for six weeks showed sperm decrease in the epididymal lumen at 10 and 30 mg/kg [46].…”
Section: Adult Effectsmentioning
confidence: 89%
See 3 more Smart Citations
“…No significant difference between sperm morphology of exposed and control groups was observed in this study; however, some sperm motility parameters were impaired in some exposed groups. In another BDE-47 study, histopathological examination of mice exposed to 1.5, 10, and 30 mg/kg of BDE-47 for six weeks showed sperm decrease in the epididymal lumen at 10 and 30 mg/kg [46].…”
Section: Adult Effectsmentioning
confidence: 89%
“…In another study, suppurative inflammation of the epididymis in mice was observed after exposure to 30 mg/kg of BDE-47 for 6 weeks [46]. Additionally proteomic and metabolomic analysis of testis tissue showed that BDE-47 can trigger the apoptosis and inflammatory pathway [46]. However, this analysis was done for a merged list of proteins and metabolites affected by either dose used in the study: 1.5, 10, and 30 mg/kg/day daily for 6 weeks.…”
Section: Inflammatory Responsementioning
confidence: 95%
See 2 more Smart Citations
“…Metabolomics, as a sensitive barometer of external stimulation and pathological insults, provides a powerful strategy for screening environmental exposures-related and adverse outcomes-related metabolites with no prior hypothesis and contributes to the characterization of their complicated mechanisms from a metabolic perspective (Huang et al, 2018;Valvi et al, 2020;You et al, 2021). To date, some metabolomics studies on PBDE exposure effects have addressed the compelling metabolic changes in the animal and cell lines models (Chi et al, 2011;Ji et al, 2019a;Tang et al, 2019;Wei et al, 2018;Xu et al, 2021;Yang et al, 2019), concerning on breast cancer (Wei et al, 2018), hepatic steatosis (Yang et al, 2019), neurotoxicity (Ji et al, 2019a;Tang et al, 2019), reproductive toxicity (Xu et al, 2021) and embryo-toxicity (Chi et al, 2011). In addition, a few studies have used metabolomics approach to investigate the underlying metabolism disorders of adverse pregnancy outcomes, such as intrauterine growth restriction (IUGR) (Favretto et al, 2012) and spontaneous preterm birth (SPB) (Elshenawy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%